P571 Vedolizumab (VDZ) real-world outcomes in ulcerative colitis (UC). (16th January 2018) - Pulusu, S S R; Srinivasan, A; Krishnaprasad, K; Cheng, D; Mogilevski, T; Flanagan, E; Keung, C; Wu, C; Prosser, R; Sawyer, E; Rizvi, Q -U -A; Su, H; et al.
Abstract: Background: In GEMINI 1, UC response to vedolizumab (VDZ) was 47% at Week 6 and 42% by Week 52. Our aim was to assess real-life outcomes for VDZ in UC. Methods: Data collected at 12 Australian (Aus), 1 UK and 2 Hong Kong (HK) centres, assessed response to VDZ at 3, 6, and 12 months using the Mayo Clinic Score (MCS, Aus/HK) or SCCAI and UCEIS (UK). Results: Two hundred and ninety-three patients (53% male, median age 38 years, 196 Aus, 93 UK, 4 HK) were assessed with similar age, disease location and duration allowing combining of data. Median MCS pre VDZ was 8 (range 2–12, n = 152) and Mayo endoscopy subscore 2 of 3 (Aus, HK). Median SCCAI was 8 (range 0–13, n = 87) and UCEIS 5 of 8 (UK). VDZ was the first biological agent in 170 of 293 (58%), prior anti-TNF use occurred in 123 [reason for switching: primary non-response (PNR) n = 46, loss of response (LOR) n = 62, side-effects (SE) n = 15; two patients with side-effects were in remission and not included for analysis]. At VDZ start, 61% taking steroids and 56% immunomodulation (IM). Response rates at 3 months: 220 of 279 (79%) overall responded, TNF-naïve 134 of 163 (82%), TNF-exposed 86 of 116 (74% p = NS). Remission rates at 3 months: 155 of 279 (55%) in clinical remission, TNF-naïve 110 of 163 (67%), TNF-exposed 45 of 116 (39%, p = 0.01). 60 of 132 (45%) patients in remission were on IM and 49 of 101 (49%) if not (NS). Six months: Overall 144 of 235 (61%) in clinical remission, TNF-naïve 97 of 131 (74%), TNF-exposed 47 of 104 (45%, p = 0.03), and 60 of 124 (48%) in endoscopic remission (MES = 0 or 1). Steroids were ceased in 61 of 136 (45%) if in remission and 23 of 85 (27%) if not ( p = 0.08). 39% (49 of 125) patients in remission were on IM and 29% (24 of 82) if not (NS). 12 months: Overall 117 of 196 (60%) were in remission, TNF-naïve 72 of 106 (68%), TNF-exposed 45 of 90 (50%, NS). No significant difference in remission rates seen between PNR, LOR, or anti-TNF naïve patients. Steroids ceased in 55 of 110 (50%) if in remission and 6 of 80 (8%) if not ( p < 0.001). Thirty-seven of 104 (36%) patients in remission were on IM and 13 of 78 (17%, p = 0.03) if not. Those in remission at 3 and 6 months, 90% (74 of 82) and 92% (96 of 104), respectively maintained remission. Smoking status did not affect response to VDZ. Colectomy occurred in 33 of 293 (11%). Adverse events occurred in 20 of 293 (7%); 2 were serious (Klebsiella sepsis and hemophagocytic syndrome). Conclusions: VDZ induced remission in 55% at 3 months and 61% at 6 months with >90% maintaining remission at 12 months. VDZ use continued for 12 months in 71% (139 of 196) with 61% in remission. Steroids were withdrawn in 50% patients in remission at 12 months. IMs might increase remission rates at 12 months. VDZ was initially more effective in anti-TNF naïve patients but differences were lost at 12 months suggesting patience may be needed in anti-TNF-exposed patients.